A Comparative Evaluation of Accommodation Strategies in Doctor-Patient Interactions in The Nupe and Yoruba Settings - Olufadi, Kifayat Gambari (English Language and Literature, 2024)
The interactional value of medical discourse, as a genre of spoken communication, is often affected by specific contextual and anthropological issues arising from the diversity in the sociocultural backgrounds of interlocutors. Apart from these factors of contextual orientation are important factors that impact on the interactional value of medical discourse. The aim of this study was to examine the characteristics of two distinct cultures within the Nigerian set-up and their impact on doctor-patient interaction. More specifically, the study examines how the anthropological characteristics of the Nupes/ Yorubas influence the adoption of accommodation strategies in medical discourses, towards the achievement of the communicative goal. Also, how power and ideology are reflected and managed in the medical discourse in these distinct cultures are critically examined in this study. To achieve the study aim, two purposively selected doctor-patient conversations in the two cultures, Yoruba and Nupe, were analysed using the tenets of Communication Accommodation Theory CAT. The study found that even though cultural difference abounds in the selected medical-discourse under investigation and has proven to be a constant factor to reckon with, the choice and use of accommodation strategies depend on the individual linguistic prowess. Despite the fact that the adoption of convergence strategies is an expected norm in medical discourse, power, which is associated with class and age difference among interlocutors often result to the use of divergence strategy.